2011
DOI: 10.1002/aenm.201100144
|View full text |Cite
|
Sign up to set email alerts
|

The Nanoscale Morphology of a PCDTBT:PCBM Photovoltaic Blend

Abstract: Organic photovoltaic devices (OPVs) based on conjugated polymers and fullerene blends offer an attractive method to produce renewable energy. It has been demonstrated that they can be manufactured on fl exible substrates and at low cost over large areas using the high volume technique of roll-to-roll printing. [1][2][3] Whilst much work has been devoted to the donoracceptor system P3HT:PCBM (poly(3-hexylthiophene):[6,6]-phenyl-C 61 -butyric acid methyl ester), attention is now turning to the use of donor mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
86
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(94 citation statements)
references
References 29 publications
7
86
0
1
Order By: Relevance
“…Staniec et al made a detailed characterization of the thermal treatment on the morphology of the PCDTBT:PCBM active layer. 89 By using neutron reflectivity to probe the depth-dependent concentration of PCBM, they found that the surface of a freshly cast thin film was enriched with PCBM, which is the opposite of what is observed with P3HT:PCBM. The thermal annealing at 70 C, did not significantly change the vertical distribution of the components and the overall crystallinity of the polymer remained relatively constant.…”
Section: Polyfluorene-based Polymermentioning
confidence: 99%
See 1 more Smart Citation
“…Staniec et al made a detailed characterization of the thermal treatment on the morphology of the PCDTBT:PCBM active layer. 89 By using neutron reflectivity to probe the depth-dependent concentration of PCBM, they found that the surface of a freshly cast thin film was enriched with PCBM, which is the opposite of what is observed with P3HT:PCBM. The thermal annealing at 70 C, did not significantly change the vertical distribution of the components and the overall crystallinity of the polymer remained relatively constant.…”
Section: Polyfluorene-based Polymermentioning
confidence: 99%
“…The T g of PCDTBT is $130 C, 90 thus, the authors argued that the 70 C annealing brought the active layer above the T g of the PCDTBT due to the presence of residual solvent, and, with time, the trapped solvent diffused out of the active layer without significantly altering the overall morphology. 89 Cyclopentadithiophene-Based Polymer Cyclopentadithiophene-based polymers are another class of promising donor materials. Poly[2,6-(4,4-bis(2-ethylhexyl)-4H-cyclopenta[2,1-b;3,4-b 0 ]-dithiophene)-alt-4,7-(2,1,3-benzothiadiazole)], PCPDTBT, is probably the most well-studied low band gap polymer.…”
Section: Polyfluorene-based Polymermentioning
confidence: 99%
“…We identify scattering at this Q value as originating from PCDTBT, specifically fi rst order scattering between neighbouring chains along the lamella direction. [34][35][36] Here, the weak signal intensity refl ects both the semi-amorphous nature of the polymer and its low concentration (20 wt%) in the blend fi lm. We highlight the three key stages in the process determined by our measurements.…”
Section: Drying Dynamics Of Pcdtbt:pc 70 Bmmentioning
confidence: 99%
“…as observed similar to the blend film prepared by CF, indicating that PC 71 BM was relatively enriched in the top surface of the blend film in both cases and the corresponding BHJ solar cells might represent relatively high photovoltaic performances accordingly [39,40]. Admittedly, this is just a possibility because the performance of PSC has a lot to do with the morphology of the active layer.…”
Section: Water Contact Angle Characterizationsmentioning
confidence: 69%
“…Using the mixed solvent of ODCB/CF (2/1, v/v) to prepare the blend film could decrease the water contact angle and the corresponding value is 103.3° ± 0.5°. Interestingly, when adding some amount of DIO to the mixed solvent, a smaller water contact angle of 100.1° ± 0.4° was observed similar to the blend film prepared by CF, indicating that PC71BM was relatively enriched in the top surface of the blend film in both cases and the corresponding BHJ solar cells might represent relatively high photovoltaic performances accordingly [39,40]. Admittedly, this is just a possibility because the performance of PSC has a lot to do with the morphology of the active layer.…”
Section: Water Contact Angle Characterizationsmentioning
confidence: 99%